Triple Nexus: leveraging development supply chains for humanitarian aid and peace in Southeast Asia – a GBV focus - Christina Plesner Volkdal (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – The purpose of this study is to emphasize the crucial role of supply chains in humanitarian and development interventions, specifically targeting gender-based violence in East Asia and the Pacific, regions prone to climate change-induced disasters. It explores optimizing development supply chains for humanitarian use, and the plausible impacts on community peacebuilding. Design/methodology/approach – By adopting an abductive approach to the action research methodology, based on 11 case studies, including intensive fieldwork in seven, this study evaluates development supply chains for their adaptability, institutionalization and flexibility to support humanitarian needs and analyzes the potential interlinkages of peacebuilding. Findings – The research uncovers the irregular and unsystematized present humanitarian efforts and highlighting a lack of advancement in development channels for implementing effective humanitarian preparedness and response. By focusing on the Triple Nexus framework and based on the findings, the study rather proposes enhancing the humanitarian supply chain, suggesting a restructured mechanism for development channels that fosters synergies across the dimensions. It intricately connects peacebuilding applying a Triple Nexus Analytical Framework, examining the potential impact on micro-level peacebuilding outcomes. Research limitations/implications – The research recognizes the challenge in conceptualizing peacebuilding within the Triple Nexus framework, calling for a nuanced understanding of peacebuilding across different levels. Contrary to expectations, the case studies yielded unexpected results, suggesting a need for a reversed approach in the applied methodology, hence advancing humanitarian supply chains with synergies to development channels that in the specific cases studies lack efficiency in their current set-up. Originality/value – This study examines the collaboration between humanitarian efforts and development initiatives and how they can collectively contribute to peacebuilding. It pushes forward the conversation on improving humanitarian preparedness by leveraging development supply chains and explores the effects of peacebuilding on local levels.